Computational aerodynamics analysis on pitching moment using ducted fan over flat plate for high altitude platform station - Muhd Arif, Nur Liyana Sabrina; Mohammad Ali, Hidayatullah; Mohd Rafie, Azmin Shakrine (Aerospace Society Malaysia, 2023)
The CyFlaP is a new invention that operates based on the principle of Magnus effect. It is essentially developed to be applied as unmanned aerial vehicle (UAV) and high altitude platform station (HAPS) for surveillance purposes that can fly in the stratosphere region. In previous study of CyFlaP, the presence of a moment force acting at the centre of its body is shown to affect its stability during flight. To address this problem, this study explores the placement of a ducted fan on both sides of the CyFlaP, which are intended to provide thrust and also help to stabilize it. For the latter purpose, a flat plate is installed at the back of the ducted fan such that the ejected flow behind it can be used to produce a lift force on the flat plate, which is then projected to counter existing pitching moment on the CyFlaP. Simulation analysis of the flow on the plate located behind the rotating ducted fan is conducted using computational fluid dynamics (CFD) software in ANSYS Workbench 2021. The simulation analysis is done with different rotational ducted fan speeds up to 5000 RPM for three cases of flat plates aspect ratio at different angles of attack ranging from 0° to 15° with fixed free stream velocity of 5 m/s. The results indicate that the increase in the aspect ratio of the flat plate will decrease the generated lift force. In contrast, the lift force is increased with higher rotational speed of the ducted fan and larger angle of attack of the plate. However, on the whole, it is found that implementing a flat plate behind the ducted fan is inadequate to oppose the existing acting moment force on the CyFlaP and hence the search for better design solution to resolve the issue is still ongoing.